Investigation of earthmoving trucks deterioration using discriminant analysis. (1st January 2012) - Marinelli, Marina; Lambropoulos, Sergios; Pantouvakis, John-Paris
Earthmoving equipment has a determinant role in the successful realisation of most civil engineering projects. However, it may suffer significant downtime due to the continuous and intense use in harsh working conditions. This downtime may be associated with certain deterioration parameters, which if known, would allow more accurate estimations to be made. For this purpose, the data sets from two large Greek construction companies containing the characteristics of 126 earthmoving trucks (capacity, age, kilometres travelled to date, maintenance class and condition level) have been analysed using discriminant analysis. The analysis allows for the assessment of the connection of each characteristic with the condition level of the sample trucks and also leads to rules that can be used for the prediction of the condition level of other trucks.